In Vitro Stability Evaluation of Different Pharmaceutical Products Containing Meropenem - Tomasello, Cristina (Hosp Pharm, 2015)
BACKGROUND: Meropenem is a beta-lactam antibiotic for treating multidrug-resistant gram-negative bacilli infections. The expiry of the drug’s patent (Merrem) allowed the production of generics to be commercialized by a few companies, including Hospira and Hikma. The stability of these medicines after reconstitution as reported on a data sheet report is 6 hours for Merrem and 1 hour for generics. OBJECTIVES: The aim of this work was to evaluate the stability profile of 3 products in 0.9% sodium chloride until 6 hours. METHODS: Six polyolefin bags (2 for each drug, stored in the light and in the dark) were prepared for every test run (n =10) at concentrations of 4 and 10 mg/mL. All solutions were stored at controlled room temperature (25°C ± 3°C) and sampled immediately after preparation and at every hour until 6 hours had passed. The concentrations, pH changes, and the visual clarity were used as stability and compatibility indicators. RESULTS: All 3 drugs retained over 95% of the initial concentration at 3 to 4 hours. At the sixth hour, all the concentrations decayed 8% to 10%. No statistical differences were observed in the percentage deviation values of the stability profile between generics and the branded drug. CONCLUSION: The stability profile of the products in polyolefin bags, at 4 and 10 mg/mL, was superimposable during the period of analysis and seems to show small values of deviation (1%-2%). These data do not affect the pharmacokinetics because these variations could be attributed to the intra- and interindividual variability between patients. The products showed the same stability, and consequently they could be used interchangeably in hospital pharmacy.